Pengaruh Promosi Penjualan dan E-Service Quality terhadap Minat Beli Ulang Produk Skincare Perawatan Wajah: (Studi Kasus Pada Pengguna E-Commerce Shopee Mahasiswa Uniska Kediri Fakultas Ekonomi) - Ria Fatmala; Anita Sumelvia Dewi; Angga Permana Mahaputra (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to explain and prove the hypothesis about whether there is an effect of sales promotion and e-service quality on repurchasing interest in facial care skincare products (a case study on e-commerce shopee users at Uniska students, Faculty of Economics). This research uses descriptive research with quantitative methods with sampling techniques, namely non-probability sampling with accidental sampling methods with a population of 536 students and a sample of 84 students. The analysis technique used is the validity test, reliability test, classical assumption test, multiple linear regression test, t test (partial), F test (simultaneous) and the determinant coefficient (R2) which is processed using the SPSS version 25 program. The results of the study obtained conclusions that sales promotion has a partial and significant effect on repurchase intention, as evidenced by the t test results obtained by the value of Sig. 0.006 <0.05. E-service quality has a partial and significant effect on repurchase intention, as evidenced by the t test results obtained by the Sig value. 0.000 < 0.05. Sales promotion and e-service quality have a simultaneous and significant effect on repurchase intention, as evidenced by the results of the F test, the value of Sig. 0.000 < 0.05.